Google Classroom as an Online Learning Facility: Students Admission at MTs Al-Ihsan Jombang - Hilyah Ashoumi; M. Nouval Analis Blonos (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to determine student acceptance of the use of Google Classroom as an online learning facility at Mts Al-Ihsan Kalikejambon Tembelang. The questions to be answered through this research are: 1) How is the student acceptance of google classroom as an online learning tool for maple SKI at MTs Al-Ihsan? 2) What is the feasibility of the Google Classroom learning facility as an SKI learning medium? This research uses R&D or development research methods. This study adheres to the model developed by Borg and Gall (2003). The development procedure in this study includes several stages (1) potential and problem analysis, (2) data collection, (3) product design, (4) design validation, (5) design improvement, (6) product testing, (7) product revision. Data collection techniques in this research were obtained by two methods of data collection, namely questionnaires and documentation. The data analysis technique used in this research is qualitative data analysis and quantitative data analysis. The research findings show that 1) students can accept it well with the average result of the questionnaires distributed that is 76% of 15 students. 2) The results of expert validation of the material through the google classroom learning facility with a feasibility percentage of 74.05%, while the results of media validation by experts are 77.14%, for the media it is declared feasible to be applied during online classroom learning through Google classroom.